COMPARISON BETWEEN SALINE AND BUFFERED SOLUTIONS: BIBLIOGRAPHIC REVIEW - Silva, Wallace Andrino; Araújo Costa, Diego Alex (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2020)
An important milestone in medicine was the development of intravenous fluids. It has an immediate impact on the outcomes of diseases, such as cholera and polytrauma patients. Its importance triggered interest in the study of the physiology and anatomy of macro and microcirculation, the creation of new fluids, as well as the impact of the type of solutions on clinical outcome. Saline solution, more known as physiological saline or normal saline solution, is one of the oldest and most used solutions in the world. Buffered solutions, such as Plasma-lyte®, Lactate Ringer, among others, which uses weak buffers and anions in its composition, proved to be more physiological, with better clinical outcomes, in a wide variety of patients. The discoveries of the anatomy and physiology of microcirculation, hydroelectrolytic and acid-base alterations specific to each disease, hyperchloremia and its harmful effects brought a wide and important discussion in the indication of each crystalloid. The type and amount of fluid to be administered in the perioperative period have a direct impact on the outcome. Buffered solutions have been presented as a superior alternative to 0.9% saline in the perioperative context.